Next generation of domestic wastewater management - Vinnerås, Björn (Frontiers in Environmental Science, 2025)
The next generation of wastewater management must go beyond centralised treatment to meet emerging environmental and regulatory demands. This study explores source separation as a complementary strategy that enables the tailored treatment of greywater, urine, and faeces. By decentralising processes and recovering resources, especially nutrients and energy, new systems can reduce greenhouse gas emissions and nutrient loads on existing infrastructure and receiving environments. Innovations in urine concentration and fertiliser production demonstrate the feasibility of turning waste into valuable products. A paradigm shift towards source-separated sanitation is essential for climate neutrality and staying within planetary boundaries.